Reactivation of tumour suppressor in breast cancer by enhancer switching through NamiRNA network. Issue 15 (30th July 2021) - Liang, Ying; Lu, Qi; Li, Wei; Zhang, Dapeng; Zhang, Fanglin; Zou, Qingping; Chen, Lu; Tong, Ying; Liu, Mengxing; Wang, Shaoxuan; Li, Wenxuan; Ren, Xiaoguang; et al.
Abstract: Dysfunction of Tumour Suppressor Genes (TSGs) is a common feature in carcinogenesis. Epigenetic abnormalities including DNA hypermethylation or aberrant histone modifications in promoter regions have been described for interpreting TSG inactivation. However, in many instances, how TSGs are silenced in tumours are largely unknown. Given that miRNA with low expression in tumours is another recognized signature, we hypothesize that low expression of miRNA may reduce the activity of TSG related enhancers and further lead to inactivation of TSG during cancer development. Here, we reported that low expression of miRNA in cancer as a recognized signature leads to loss of function of TSGs in breast cancer. In 157 paired breast cancer and adjacent normal samples, tumour suppressor gene GPER1 and miR-339 are both downregulated in Luminal A/B and Triple Negative Breast Cancer subtypes. Mechanistic investigations revealed that miR-339 upregulates GPER1 expression in breast cancer cells by switching on the GPER1 enhancer, which can be blocked by enhancer deletion through the CRISPR/Cas9 system. Collectively, our findings reveal novel mechanistic insights into TSG dysfunction in cancer development, and provide evidence that reactivation of TSG by enhancer switching may be a promising alternative strategy for clinical breast cancer treatment.